MULTI-OBJECTIVE EVOLUTIONARY ALGORITHMS: FOUNDATION, DEVELOPMENT AND OPEN ISSUES - Lâm, Bùi Thu (Journal of Computer Science and Cybernetics, 2018)
Evolutionary computation (EC) has been a fascinating branch of computation inspiredby a natural phenomenal of evolution. EC enables computer scientists to design eective algorithmsdealing dicult problems. This paper focuses on a special class problem called multi-objective optimizationproblems and evolutionary algorithms designed for it. We will overview the development ofmulti-objective evolutionary algorithms (MOEAs) over the years and problem diculties and thenindicate the open problems in this area. Our chief goal is to provide readers reference material in thearea of multi-objective evolutionary algorithms